Effects of a severe drought on Quercus ilex radial growth and xylem anatomy - Gil-Pelegrín, Eustaquio; Corcuera, Leyre; Camarero, Jesús Julio (Trees - Structure and Function, 2004)
We assessed the response of Quercus ilex subsp. ballota to the severe summer drought recorded in 1994 in NE Spain through the study of changes in radial growth and wood anatomy. We selected a coppice stand in the Iberian Peninsula, which is characterized by a Mediterranean climate under continental influence. We measured internode length, tree-ring width, mean and maximum vessel diameter, and vessel density for 1981– 1997. The annual predicted hydraulic conductance (Kh) was calculated following Hagen-Poisseuille’s law. We compared the tree-ring width, vessel diameter and Kh of Q. ilex subsp. ballota and co-existing ring-porous oaks (Q. faginea, Q. pyrenaica) for a dry summer (1994) and a wet summer (1997). To evaluate the drought-resistance of xylem for Q. ilex subsp. ballota (dominant under continental conditions) and Q. ilex subsp. ilex (dominant in mild areas) we determined vulnerability curves. Dimensionless indices of internode length, tree-ring width, and vessel density were compared with climatic data (monthly total precipitation and mean temperature) using correlation analyses. Internode length, tree-ring width, Kh, and mean and maximum vessel diameter declined in 1994. According to vulnerability curves, Q. ilex subsp. ballota showed a greater drought resistance than Q. ilex subsp. ilex. During the year of growth, we found a positive influence of January and June–August precipitation on the internode length, tree-ring width, and vessel density. The response of Q. ilex subsp. ballota radial-growth to summer drought was comparable to that of Q. faginea latewood. Overall, growth and wood anatomy of Q. ilex subsp. ballota showed a plastic response to drought.
Keywords: cavitation; climate; Dendroecology; vulnerability curve; Xylem

Drought resistance of 2-year-old saplings of Mediterranean forest trees in the field: relations between water relations, hydraulics and productivity - Gullo, M A Lo; Salleo, S; Rosso, R; Trifilo, P (Plant and soil, 2003)
Drought resistance was examined for 2-year-old saplings of Ceratonia siliqua L., Olea oleaster Hoffmgg. et Link., Quercus suber L. and Q. pubescens Willd. growing in the ﬁeld in Sicily, with the aim of testing their possible use in the reforestation of degraded areas. To this purpose, leaf conductance to water vapour (gL), transpiration rate (EL), relative water content (RWC) and water potential (L) were measured between pre-dawn and sunset, monthly from May to November. Parallel measurements of loss of hydraulic conductance of twigs of the current year (PLC) were made together with an estimate of whole-plant hydraulic conductance (KPLANT) on the basis of the ratio of maximum EL to (PD − MIN), where PD is pre-dawn L and MIN is the minimum diurnal L. C. siliqua saplings maintained high gL throughout the study period with high RWC (over 90%) and L. They grew rapidly and increased their foliage area (AL) by over 60% from May to winter rest. This was accompanied by low twig PLC (about 20% in September) resulting in high KPLANT all through the study period. In contrast, O. oleaster saplings underwent distinct dehydration in July, i.e. they showed stomatal closure due to a drop in RWC (to 75%) and L (to the turgor-loss point). This was apparently due to twig cavitation, resulting in a strong decrease of KPLANT. Plants, however, tolerated summer drought, and showed growth (AL increased by 15% from May to November). Saplings of Q. suber and Q. pubescens were much more vulnerable to twig cavitation (PLC was 35–48% from June to November) than the other two species, and their average KPLANT was lower. Saplings of Q. suber and Q. pubescens grew only during the wet spring period, and no new foliage was produced thereafter. Changes in twig hydraulic conductance played a dominant role in determining changes in KPLANT in that the two variables were well correlated to each other (r = 0.68 for P = 0.001). We conclude that C. siliqua is an ideal candidate for reforestation of Sicilian degraded areas as is O. oleaster that, however, requires some additional water supply in the summer, at least during the early years after plantation. In wetter locations of Sicily, to an altitude between 0 and 500 m, Q. suber and Q. pubescens can be used for reforestation with expected higher competitiveness of the latter over the former species.
Keywords: cavitation; Drought resistance; hydraulics; Mediterranean trees; Reforestation; water relations

Ultrasound acoustic emissions from bark samples differing in anatomical characteristics - Kikuta, S B (PHYTON-ANNALES REI BOTANICAE, 2003)
This study examines ultrasound acoustic emissions (UAE) from various bark types differing in anatomical characteristics. UAE were detected in dehydrating bark strips from twigs of two conifers (Pinus nigra ARNOLD, Taxus baccata L.), and four woody dicotyledons (Hedera helix L.. Malus sylvestris MILL., Sambuctis nigra L., and Tilia platyphyllos SCOP.) with varying contents of dead mechanical elements in the cortex and in the secondary phloem. If filled with water, non-conducting bark elements (sclereids, fibre-sclereids, secondary phloem fibres and periderm cells) emitted ultrasound during dehydration. Signal production varied between the species and the bark layers studied. Pressure infiltration increased the number of UAE conspicuously. UAE were also registered from infiltrated sections of bottle cork (Quercus suber L.) and infiltrated walnut shells (Juglans regia L.) built of sclereids only and characterised by lignified secondary cell walls. Stems of Sphagnum sp. emitted UAE, probably originating in hyalocysts, dead non-conducting water storage cells in the leaves. Living cells (inner epidermes of bulb scales of Allium cepa L. and collenchyma, strands from the herbaceous stern of Lamium maculatum L.) produced only very few UAE. The results suggest that ultrasound acoustic emissions during dehydration do not only occur in cavitating conducting xylem elements but also in non-conducting, dead cells with thick walls.
Keywords: Bark; cavitation; Dehydration; fibres; infiltration; periderm; sclereids; secondary phloem; ultrasound acoustic emissions

Seasonal embolism and xylem vulnerability in deciduous and evergreen Mediterranean trees influenced by proximity to a carbon dioxide spring - Tognetti, Roberto; Longobucco, Anna; Raschi, Antonio (Tree Physiology, 1999)
We investigated how proximity to natural CO2 springs affected the seasonal patterns of xylem embolism in Quercus ilex L., Quercus pubescens Willd., Fraxinus ornus L., Populus tremula L. and Arbutus unedo L., which differ in leaf phenology and wood anatomy. Xylem embolism was evaluated in both artificially dehydrated branches and in hydrated apical branches collected at monthly intervals during a 20-month sampling period. Initial specific hydraulic conductivity was also evaluated. We found species-dependent differences in xylem hydraulic properties in response to elevated CO2 concentration. Populus tremula was the most embolized and A. unedo was the least embolized of the species examined. Effects of elevated CO2 were significant in Q. pubescens, P. tremula and A. unedo, whereas the overall response to elevated CO2 was less evident in F. ornus and Q. ilex. Specific hydraulic conductivity differed among species but not between sites, although the interaction between species and site was significant. Differences in xylem vulnerability between trees growing near to the CO2 spring and those growing in control areas were small. Although differences in hydraulic properties in response to elevated CO2 concentration were small, they may be of great importance in determining future community composition in Mediterranean-type forest ecosystems. The possible causes and ecological significance of such differences are discussed in relation to elevated CO2 concentration and other environmental conditions.
10.1093/treephys/19.4-5.271
Keywords: cavitation; CO2 springs; diffuse-porous; Global change; hydraulic conductivity; Mediterranean-type ecosystems; ring-porous; semiring-porous

Vulnerability of xylem to embolism in relation to plant hydraulic resistance in Quercus pubescens and Quercus ilex co-occurring in a Mediterranean coppice stand in central Italy - Tognetti, R; Longobucco, A; Raschi, A (New Phytologist, 1998)
The seasonal patterns of xylem embolism and xylem transport properties in Quercus pubescens Willd. and Quercus ilex L. trees growing in a natural mixed coppice stand in conditions of severe water stress were investigated. Xylem embolism was evaluated in both dehydrating branches and in apical twigs during a whole year. Measurements of xylem water potential were conducted from predawn to sunset on selected sunny days. On the same days, diurnal courses of leaf conductance were monitored. Measurements of half-hourly sap flow were made by the heat-pulse technique throughout the summer. At the onset of summer, a sharp decrease in water potential was observed in both species. Full recovery of water potentials was observed for both species after the first major rainfall event in September. Both experienced serious embolism throughout the year, ranging between minima of c. 60% (expressed as percentage loss of hydraulic conductivity) after the rains in autumn and after bud burst in spring, and maxima of c. 80% during summer and after freezing-thawing events during the winter season. A significant negative linear relationship was found between water potential and xylem embolism in branches dehydrating in air for Q. pubescens and Q. ilex. Q. pubescens had greater efficiency in hydraulic transport (higher specific conductivity and leaf specific conductivity) by the xylem than Q. ilex. In June, leaf conductance was high early in the morning and decreased gradually during the day. Midday depression of leaf conductance, as a result of high evaporative demand combined with water deficit, was observed in both species. In August, leaf conductance of both species was greatly reduced, as water potential dropped to extremely low values, and the stomata were almost completely closed during the afternoon. No hysteresis resulting from plant capacitance was observed in the relationship between shoot water potential and sap flow. Q. pubescens exhibited very high values of whole-tree hydraulic resistance between July and September, whereas Q. ilex generally showed lower values. The effect of soil moisture depletion on the relationship between sap flow and shoot water potential appears as a lowering of water potential at zero flow. A significant decrease of whole-tree hydraulic resistance in both species was observed with the onset of the autumn, preceding the partial recovery of twig hydraulic conductivity. The results demonstrate that both Q. pubescens and Q. ilex, although highly tolerant of severe water stress and tissue dehydration, operate at the limits of safety which are surpassed under severe droughts, and prolonged climatic stress might predispose these Quercus species to decline.
Keywords: cavitation; Drought; Hydraulic resistance; Quercus ilex L.; Quercus pubescens Willd.; water relations; xylem embolism